Biofilm and pathogenic factor analysis of Gardnerella vaginalis associated with bacterial vaginosis in Northeast China - Ma, Xiaolu; Wang, Xiaoxi; Ye, Shengna; Liu, Jinnan; Yuan, Hong; Wang, Nan (Frontiers in Microbiology, 2022)
Introduction Gardnerella vaginalis is a major pathogen responsible for bacterial vaginosis (BV). However, the recurrence of infection and the antibiotic resistance of biofilms remain significant challenges for the treatment of BV. In this study, we aimed to analyze the pathogenic factors and drug sensitivity associated with the clinical treatment of BV in Northeast China. Methods Subgroups were identified by clade-specific polymerase chain reaction (PCR). Biofilm formation was measured by crystal violet staining, confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). The inhibition and eradication of biofilm formation were measured by XTT and broth recovery-based methods. Results Of the 24 samples of G. vaginalis, 11 samples and American Type Culture Collection (ATCC) 14018 formed biofilms; the remainder did not. The positive rates of detection for the sialidase A and vly genes in the 24 G. vaginalis samples were 100% and 79.2%, respectively. Moreover, 21 samples (87.5%) showed resistance to metronidazole and 16 (66.7%) presented with sensitivity towards clindamycin. The biofilm MIC80 (BMIC80) of metronidazole for ATCC14018 was 16 μg/ml while that of clindamycin was 0.125 μg/ml. The minimum biofilm eradication concentration (MBEC) of metronidazole was > 256 μg/ml while that of clindamycin was > 2 μg/ml. Discussion Our results revealed that G. vaginalis is more resistant to metronidazole than clindamycin and neither metronidazole nor clindamycin are able to effectively eradicate vaginal biofilms. Thus, the role of antibiotics and biofilms in BV requires further investigation.